(untitled) (The Journal of Building and Land Development, 2025)
This study examined the potential of chelating agents, Ethylenediaminetetraacetic Acid and Citric Acid, to enhance phytoremediation of Pb, Cu, and Zn in contaminated soil using S. jacquemontii. A greenhouse pot experiment was conducted to evaluate the effects of EDTA and CA on biomass production and metal uptake. Soil contaminated with metals at concentrations of 300 mg/kg and 600 mg/kg were treated with chelates at the rate of 3 mmol/kg or 7 mmol/kg, while a control group received metals without chelating agents. Each treatment was triplicated to ensure reliability and accuracy in the results. Results demonstrated that both EDTA and CA significantly enhanced metal uptake (P<0.05) while reducing biomass production compared to the control. EDTA exhibited a stronger influence on metal uptake and biomass reduction than CA. The application of chelates improved the efficiency of phytoremediation by reducing the time required to lower metal concentration to Tanzanian regulatory limits (150mg/kg for Zn and 200mg/kg for Cu and Pb). Overall, EDTA and CA significantly enhanced phytoremediation efficiency (0.7%–71% improvement) for Pb, Zn, and Cu by reducing treatment duration. A pilot study on heavy metal-contaminated soils in mining areas is recommended to test the performance of plants under ambient conditions. Keywords: Soil contamination, Plant, Concentration, EDTA, CA